So many P's!

Suppose \(a,b,c\) are three numbers in G.P. If the equations \(ax^2+2bx+c=0\) and \(dx^2+2ex+f\) have a common root, then \(\frac{d}{a} , \frac{e}{b} , \frac{f}{c}\) are in :

  • A.P.

  • G.P.

  • H.P.

  • none of the above.

Note: A.P.,G.P. and H.P. above indicate the arithmetic, geometric and harmonic progressions.

Note by Paramjit Singh
4 years, 4 months ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

Consider two equations,
\(E_{1} : a_{1}x^2 + b_{1}x + c_{1}\)
\(E_{2} : a_{2}x^2 + b_{2}x + c_{2}\)
If they have a common root say \(\alpha\), then we can say that,
\(a_{1}\alpha^2 + b_{1}\alpha + c_{1} = 0\)
\(a_{2}\alpha^2 + b_{2}\alpha + c_{2} = 0\)
Solving them simultaneously for \(\alpha\) and \(\alpha^2\) and eliminating \(\alpha\) , we get an equation of the form,
\((a_{1}c_{2} - a_{2}c_{1})^{2} = (b_{1}c_{2} - b_{2}c_{1})(a_{1}b_{2} - a_{2}b_{1}) \)
Here, \(a_{1} = a, b_{1} = 2b, c_{1} = c, a_{2} = d, b_{2} = 2e, c_{2} = f \)
Substituting the values, we get,
\( (af - dc)^2 = 4(bf - ce)(ae - bd) \)
\((ac)^2(\frac{f}{c} - \frac{d}{a})^2 = 4ab^2c(\frac{f}{c} - \frac{e}{b})(\frac{e}{b} - \frac{d}{a}) \)

\( (\frac{f}{c} - \frac{d}{a})^2 = 4(\frac{f}{c} - \frac{e}{b})(\frac{e}{b} - \frac{d}{a}) \) (As \(a,b,c\) form a geometric progression)

Let \( \frac{d}{a} = l, \frac{e}{b} = m, \frac{f}{c} = n \). Therefore the above equation can be written as,

\((l - n)^2 + 4nl = 4mn + 4lm - 4m^2\)
\((l + n)^2 - 2\times2m(l+n) + (2m)^2 = 0\)
\((l + n -2m)^2 = 0\) which implies \(2m = l + n.\)
Therefore, they form an arithmetic progression.

Sudeep Salgia - 4 years, 4 months ago

Log in to reply

Great!

Paramjit Singh - 4 years, 4 months ago

Log in to reply

a p

Tejasvi Sharma - 4 years, 3 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...